2018
DOI: 10.1371/journal.pone.0191499
|View full text |Cite
|
Sign up to set email alerts
|

Short term dynamics of the sputum microbiome among COPD patients

Abstract: Chronic obstructive pulmonary disease (COPD) is an inflammatory disorder characterized by incompletely reversible airflow obstruction. The complexity of the lung microbial community in COPD patients has been highlighted in recent years. Evidence suggests that transplantation, medications, age, and disease severity influence microbial community membership. However, the dynamics of the lung microbiome in stable COPD patients remain poorly understood. In this study, we completed a longitudinal 16S ribosomal RNA s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 32 publications
(62 reference statements)
2
9
0
1
Order By: Relevance
“…This suggests that bacterial infection at exacerbation may be a key driver of the frequent exacerbator phenotype rather than viruses and that, as exacerbation frequency increases, a higher proportion of events in an individual is likely to be bacterially related. This effect was not seen at stable state, which is possibly indicative of a relatively constant microbiome, as reported previously in clinically stable COPD patients [10, 15]. In terms of viral infections, these are deemed to be stochastic events that occur following transmission and are identified less frequently than bacterial infection during an exacerbation [16].…”
Section: Discussionsupporting
confidence: 60%
“…This suggests that bacterial infection at exacerbation may be a key driver of the frequent exacerbator phenotype rather than viruses and that, as exacerbation frequency increases, a higher proportion of events in an individual is likely to be bacterially related. This effect was not seen at stable state, which is possibly indicative of a relatively constant microbiome, as reported previously in clinically stable COPD patients [10, 15]. In terms of viral infections, these are deemed to be stochastic events that occur following transmission and are identified less frequently than bacterial infection during an exacerbation [16].…”
Section: Discussionsupporting
confidence: 60%
“…There are few longitudinal studies examining the change of the lung microbiome over time. Most of the studies examine microbiome differences between exacerbations and stable state [44][45][46]. There is only one study [44] examining the microbiome dynamics in clinically stable COPD patients (Stage 2), which shows a stable composition in the microbiome in the short-term (2 days period), in contrast to an increasing variability in the long-term re-assessment (9 month period).…”
Section: Microbiome Heterogeinity and Diversity In Stable Copdmentioning
confidence: 99%
“…Sinha et al collected repeated induced sputum samples from four stable patients ith COPD over 9 months. They reported the stability of bacterial composition and diversity over 2 days, with increased variability over 9 months 78. In a larger longitudinal cohort (n=101), Mayhew et al found relative stability in microbial composition in a participant subset,51 while those with more variability were more likely to have higher exacerbation frequency.…”
Section: Introductionmentioning
confidence: 99%